USE OF SYNERGETIC APPROACH TO STUDY THE CONCEPT OF AN IDEAL PERSON OF ALISHER NAVOI BASED ON THE EXAMPLE OF THE WORK “MAHBUB UL-KULUB” (Аль-Фараби, 2023)
Abstract: This article attempts to shed light on the study of a perfect personality based on the synergetic approach on one of the key works but yet to be studied in this context, “Mahbub ul-kulub”, which is a work of literature by a prominent poet and thinker known as Alisher Navoi. In the work of Navoi, the idea and notion of a perfect person is developed through the study of the edifications given by the author on the upbringing and spiritual improvement of representatives of various groups and layers of society of ancient times. The poet describes the behavioral characteristics of various social groups of his time, and explains in more detail in comparison to his other works, which of the qualities are worth assimilating, and which ones should be abstained from. The thinker emphasizes positive qualities which are important for achieving harmony in life, and also encourages readers to get rid of negative qualities. In this way, the poet develops noble qualities in readers and encourages them on the path to self-improvement. A detailed study of the work of the great thinker shows the relevance of his teachings for our time as well.Key words: synergetics, the principle of the simple in the complex, the principle of the complex in the simple, self-organization, the influence of the future on the present, order parameters, bifurcation points.